Bilirubin-induced inflammatory response, glutamate release, and cell death in rat cortical astrocytes are enhanced in younger cells - Falcao, AS (2015)
Unconjugated bilirubin (UCB) encephalopathy is a predominantly early life condition resulting from the impairment of several cellular functions in the brain of severely jaundiced infants. However, only few data exist on the age-dependent effects of UCB an